Subduction‐Legacy and Olivine Monitoring for Mantle‐Heterogeneities of the Sources of Ultrapotassic Magmas: The Italian Case Study. (14th March 2023) - Günther, Jennifer; Prelević, Dejan; Mertz, Dieter F.; Rocholl, Alexander; Mertz‐Kraus, Regina; Conticelli, Sandro
Abstract: The origin of Italian kamafugites and lamproites is a matter of debate, not least due to their "crustal signature" displayed by trace element compositions and isotopic ratios, but also due to puzzling geodynamic significance. We combine in situ EMPA and LA‐ICP‐MS analyses with in situ analyses of oxygen isotopes (SIMS) on olivine from the Pleistocene San Venanzo kamafugites and Torre Alfina lamproites. Lamproitic olivine shows extremely high Mg# and Ni concentrations whereas Ca and Mn concentrations are low. Their δ 18 OV‐SMOW values are very high up to +11.5 ‰. In kamafugites we recognize three genetically different olivine groups: (a) phenocrystic one with high Mg#, very low Ni, high Ca and Mn. Values of δ 18 OV‐SMOW are up to +10.9 ‰; (b) melt‐related xenocrystic grains that compositionally resemble lamproitic olivine; (c) skarn‐related almost pure forsterite of extreme δ 18 OV‐SMOW ∼27 ‰, with negligible amounts of minor and trace elements. The melting and crystallization conditions of Italian kamafugites and lamproites indicate compositionally heterogeneous mantle sources on very small scales. Distinct geochemical features of the olivine macrocryst populations observed in kamafugite point to a range of processes occurring both within the magma storage and transport system. We suggest that the diversity of metasomatic agents was involved in mantle processes on local scales, coupled with magma mixing and/or the uptake of xenocrysts during magma ascend. Key Points: Using olivine composition, we observe small‐scale mantle heterogeneity resulted from the recycling of the different sediment compositions